THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND MOTIVATION TOWARDS STUDENT’S ENGLISH LEARNING ACHIEVEMENT At state vocational high schools in karawang - Asep Darojatul Romli; Asep Jamaludin (Universitas Buana Perjuangan Karawang, 2017)
ABSTRACT The purpose of research is to know and explain the effect of emotional intelligence on motivation, to know and explain the effect of emotional intelligence on English learning achievement, to know and explain the influence of motivation ability on English learning achievement and to know and explain the influence of emotional intelligence on learning achievement English through motivation. The research method used is survey method. Population in this research is all students of class X of first semester of SMKN 1 Karawang. The sampling technique used is cluster random sampling, the sample is taken randomly according to the class that has been formed. So, the sample in this study as many as 18 people from the total population of 192 people. The research instrument consists of three types of tests, namely the questionnaire of emotional intelligence, motivation questionnaire and English achievement test with the subject of the circle. Analysis of statistical data to test the hypothesis in this study using Path Analysis (Path Analysis). Statistic test is used t test. The results showed: (1) direct influence of emotional intelligence on motivation, (2) direct influence of emotional intelligence on English learning achievement, (3) direct influence of emotional intelligence to English learning achievement and (4) indirect effect of lateral thinking ability toward English learning achievement through creative thinking ability. Keywords: Emotional Intelligence, Motivation and English learning achievement